The basic and applied aspects of superoxide dismutase - Bafana, Amit; Dutt, Som; Kumar, Arun; Kumar, Sanjay; Ahuja, Paramvir S. (Journal of molecular catalysis. B, Enzymatic, 2011)
[Display omitted] ▶ The review summarizes various basic aspects of SOD such as its evolution, types, cellular and phylogenetic distribution, physiological importance in different organisms, mechanism of action, biochemical properties, and structural features which are responsible for its robust nature. ▶ The review also summarizes various applied aspects of SOD such as its performance in therapeutic clinical trials, therapeutic SOD products available in the market and their intended applications, commercial patent filings, and the potential reasons for failure of therapeutic SOD products. ▶ Different physico-chemical and biochemical modifications that can improve the efficiency of SOD have also been discussed. Superoxide dismutase (SOD) is among the most potent antioxidants known in nature and is an important constituent of cellular defence against oxidative stress. The enzyme shows several interesting properties like very high catalytic rate of reaction and high stability to physico-chemical stress. It has also attracted widespread interest due to its therapeutic potential. Oxidative stress is known to be involved in pathophysiology of several diseases and SOD supplementation has been shown to be beneficial in treatment or prevention of such diseases. However, it is yet to be developed into effective, reliable and safe antioxidant therapy. Current review focuses on the physiological importance of SOD, and developments and obstacles in its therapeutic applications for treatment of various disorders. The review also summarizes SOD-based products and patents, its potentiation to improve efficacy, and major clinical trials of SOD in human subjects. Besides, latest literature on phylogeny and biochemistry of the enzyme is also reviewed.